Implementation of IoT-Based Soil Moisture Monitoring System for Chili Plants - Munawaroh, Maysani; Maulindar, Joni; Erlinawati, Mira (Journal of Artificial Intelligence and Software Engineering, 2025)
Unstable soil moisture is a major challenge in chili cultivation, especially with climate change and limited water resources. To address this, the study developed an Internet of Things (IoT)-based soil moisture monitoring system with automatic irrigation. The system utilizes an ESP32 microcontroller, YL-69 moisture sensor, and the Blynk app for real-time monitoring and control via smartphone. The development followed the Waterfall method, covering requirement analysis, system design, implementation, and testing. Results showed the system accurately detects soil moisture, activates the water pump automatically based on threshold levels, and provides manual control options. The Blynk interface effectively displays real-time data, watering time, duration, and historical graphs with responsive and stable performance.